The novel BH-3 mimetic apogossypolone induces Beclin-1- and ROS-mediated autophagy in human hepatocellular cells - Cheng, P (Nature Publishing Group, 2013)
Apogossypolone (ApoG2), a novel derivative of gossypol, exhibits superior antitumor activity in Bcl-2 transgenic mice, and induces autophagy in several cancer cells. However, the detailed mechanisms are not well known. In the present study, we showed that ApoG2 induced autophagy through Beclin-1- and reactive oxygen species (ROS)-dependent manners in human hepatocellular carcinoma (HCC) cells. Incubating the HCC cell with ApoG2 abrogated the interaction of Beclin-1 and Bcl-2/xL, stimulated ROS generation, increased phosphorylation of ERK and JNK, and HMGB1 translocation from the nucleus to cytoplasm while suppressing mTOR. Moreover, inhibition of the ROS-mediated autophagy by antioxidant N-acetyl-cysteine (NAC) potentiates ApoG2-induced apoptosis and cell killing. Our results show that ApoG2 induced protective autophagy in HCC cells, partly due to ROS generation, suggesting that antioxidant may serve as a potential chemosensitizer to enhance cancer cell death through blocking ApoG2-stimulated autophagy. Our novel insights may facilitate the rational design of clinical trials for Bcl-2-targeted cancer therapy.